Environmental transitions : transformation and ecological defense in Central and Eastern Europe - Pavlínek, Petr, 1963-; Pickles, John, 1952- (Routledge, 2000)
This is a detailed and comprehensive account of the environmental changes in Central and Eastern Europe, both under state socialism and during the period of transition to capitalism.